Urban Sprawl and Spatial Population Estimation Using HighResolution Satellite Imagery in the Mouila Catchment Areas (Ngounié-Gabon) - Glenn-Freddy Mihindou Mihindou; Dieu-Donne Mouketou Tarazewicz; Annie Beka Beka (European Scientific Journal, ESJ, 2026)
Since the 1990s, Gabon has faced numerous difficulties in conducting its population censuses due to technical, financial, institutional and political reasons, as well as widespread disputes over the data once these censuses are completed. Indeed, the country is often faced with repeated delays and postponements between censuses, officially attributed to organisational constraints. Furthermore, the country is facing alarming urbanisation, particularly in the management of its catchment areas, which are subject to uncontrolled urban development, thereby exacerbating the risk of flooding. The aim of this study is therefore to assess urban dynamics and to estimate and model the spatial distribution of the population within the Mouila catchment areas in the Ngounié province of Gabon. In light of the challenges posed by urban expansion and traditional Gabonese censuses, we will rely on a 2008 orthophoto and a high-resolution SAS Planet 2023 image to manually digitise built-up areas in QGIS in order to produce our urban sprawl map. The population was estimated by assigning 5 people per built unit, then spatialised using the ordinary kriging geostatistical method. The results reveal a 31.4% increase in built units and a spatial expansion of population density in the Manvouka, Doufoura, Doussama and Dourougni basins respectively. These extensions have developed from the city centre outwards towards the periphery. These very high densities follow the distribution of basic infrastructure. This satellite-based geostatistical approach offers a robust alternative for spatial planning and catchment management in a context of rapid urbanisation.